Experienced and Inexperienced Secondary-School English Teachers’ Strategies and Challenges in Teaching Speaking Using Blended Learning - Faisal, Faisal; Rakhmasari, Juwita (Universitas Negeri Semarang, 2024)
This study investigated the strategies and challenges of implementing blended learning in teaching speaking instructional activity at the secondary school level in the Indonesian context. It employed in-depth semi-structured interviews to gain insights into the challenges and strategies encountered by two experienced and two inexperienced English teachers when implementing blended learning. The study findings suggest that the teachers from both groups reported similar strategies and challenges in their speaking instructional activities. Concerning the similarities, they reported using technological-based learning tools and encountering challenges regarding students’ linguistic competencies and infrastructures. Both teacher groups differed in their reported implementations of blended learning and applications of communicative instructional strategies. The study contributes to a better understanding of English language instruction in the Indonesian context. It provides valuable insights for English language teachers and educators in designing effective language teaching programs that align with the standards outlined in the Indonesian curriculum documents. It finally recommends that professional development programs focus on improving teachers’ teaching skills in utilizing appropriate educational technology and communicative activities.